Influence of shade regimes on photosynthetic rate and stomatal characters of ginger (Zingiber officinale R.) - Ravi, K Ajithkumar, B K Jayachandran, V (Journal of Spices and Aromatic Crops, 2002)
The study conducted in the influence of shade regimes on photosynthetic rate and stomatal characters of ginger (Zingiber officinale R.) indicated that the highest photosynthetic rate was in plants grown under open condition followed by plants grown at 20 to 40 per cent shade levels. Regression coefficient analysis demonstrated that photosynthetic rate, stomatal conductance, transpiration rate, stomatal index and stomatal frequency significantly reduced linearly with increasing level of shade, whereas stomatal resistance increased linearly with increasing level of shade. The enhanced rhizome yield under low levels of shade (20 and 40 per cent) copared to open condition (where photosynthetic rate was maximum) may be mainly due to the higher leaf area resulted in the plants grown under 20 and 40 per cent shade levels.